2013
DOI: 10.1007/s11207-013-0395-4
|View full text |Cite|
|
Sign up to set email alerts
|

Observations of a Quasi-periodic, Fast-Propagating Magnetosonic Wave in Multiple Wavelengths and Its Interaction with Other Magnetic Structures

Abstract: We present observations of a quasi-periodic fast-propagating (QFP) magnetosonic wave on 23 April 2012, with high-resolution observations taken by the Atmospheric Imaging Assembly onboard the Solar Dynamics Observatory. Three minutes after the start of a C2.0 flare, wave trains were first observed along an open divergent loop system in 171Å observations at a distance of 150 Mm from the footpoint of the guiding loop system and with a speed of 689 km s −1 , then they appeared in 193Å observations after their inte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
42
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 65 publications
4
42
0
3
Order By: Relevance
“…Previous works on QFP wave trains Shen et al 2013;Shen & Liu 2012;Yuan et al 2013) showed an intimate connection between the formation and propagation of QFP wave trains and the time variability of the flaring energy release. In particular, of interest are quasi-periodic pulsations (QPP) in the flare light curve.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Previous works on QFP wave trains Shen et al 2013;Shen & Liu 2012;Yuan et al 2013) showed an intimate connection between the formation and propagation of QFP wave trains and the time variability of the flaring energy release. In particular, of interest are quasi-periodic pulsations (QPP) in the flare light curve.…”
Section: Discussionmentioning
confidence: 95%
“…The observed disturbances were interpreted in terms of fast magnetoacoustic waves driven quasi-periodically at the base of the flaring region (Ofman et al 2011). Other detailed observations are reported by Shen & Liu (2012) and Shen et al (2013), who demonstrated an intimate association with the flare The movies are available in electronic form at http://www.aanda.org energy releases and the role of magnetic loop structures in guiding these waves. Yuan et al (2013) also observed quasiperiodic propagating fast wave trains associated with flaring radio emission.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…Previous observational studies indicated that the excitation of QFP waves include several possible mechanisms, including 1) the nonlinear energy-releasing processes in the magnetic reconnection process of flares (e.g., Liu et al 2011;Shen & Liu 2012b;Shen et al 2013aShen et al , 2018c, 2) the leakage of photospheric pressure-driven oscillations into the corona (e.g., Shen & Liu 2012b), and 3) the dispersive evolution of an initially broad-band disturbance in inhomogeneous medium (e.g., Nisticò et al 2014;Shen et al 2018b,d). For the present case, by analyzing the periods of the associated flare we find that the periods of the QFP wave and the associated flare showed large difference.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The typical apparent (projected) speeds of the disturbances were found to exceed several hundred km s´1, and the periods are several tens of seconds (see e.g. Shen et al 2013, for another recent event). Also, detailed analysis revealed the association of rapidly propagating EUV disturbances with impulsive energy releases (Shen & Liu 2012) and the wave-train nature of the disturbances (Yuan et al 2013).…”
Section: Introductionmentioning
confidence: 99%